Note on the point-splitting procedure to evaluate vacuum fluctuation in certain cylindrically symmetric backgrounds - Brevik, I.; Matsas, G. E A [UNESP]; Moreira, E. S. [UNESP] (American Physical Society (APS), 1998)
We reexamine the two-point function approaches used to study vacuum fluctuation in wedge-shaped regions and conical backgrounds. The appearance of divergent integrals is discussed and circumvented. The issue is considered in the context of a massless scalar field in cosmic string spacetime.